Critical phenomenon during photoinitiated gelation at different temperatures: A Photo-DSC study - Dogruyol, Zekeriya; Arsu, Nergis; Dogruyol, Sevnur Keskin; Pekcan, Onder (ELSEVIER SCIENCE SA, 2011)
The behaviour of photoinitiated radical polymerization of an 80 wt% epoxy diacrylate (EA) and 20 wt% tripropyleneglycoldiacrylate (TPGDA) mixture with 2-mercaptothioxanthone (TX-SH) photoinitiator was studied at different temperatures by using photo-differential scanning calorimetric (Photo-DSC) technique. All photopolymerization reactions were carried out under the same conditions. It was observed that all conversion curves during gelation at different temperatures present nice sigmoidal behaviour which suggests the application of the percolation model. Observations around the critical time, called the glass transition point (t(g)), taken to reach the maximum rate of polymerization (Rp(max)) show that the gel fraction exponent (beta) obeyed the percolation model. The produced beta values were found to be around 0.50, predicting that the system under consideration belongs to the same universality class. However. Rp(max) and the final conversion (C(s)) values were found to increase when the temperature was increased up to a certain value. On the other hand, t(g) values decreased and became saturated as the temperature was increased. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Percolation; Temperature; Epoxy acrylate; Photo-DSC; Critical exponent; FREE-RADICAL POLYMERIZATION; MOLECULAR-SIZE DISTRIBUTION; CRITICAL EXPONENTS; PHOTOPOLYMERIZATION KINETICS; GLASS-TRANSITION; RATE CONSTANTS; POLYMERS; VISCOELASTICITY; METHACRYLATE; Chemistry; Materials Science